2014
DOI: 10.1152/ajpregu.00033.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and erectile dysfunctions in the Type 2 diabetic Goto-Kakizaki rat

Abstract: Despite the fact that urogenito-sexual complications significantly impact the quality of life of diabetic patients, a robust in vivo experimental model is lacking. Bladder and erectile function in the Type 2 diabetic Goto-Kakizaki (GK) rat and responses to standard-of-care treatments for each disorder have been assessed. GK rats (n = 25, 18-wk-old, GK/Par colony) and age-matched Wistar rats (n = 23), characterized for their metabolic parameters, were used. Bladder function was assessed by cystometry in conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
1
14
0
4
Order By: Relevance
“…glucose clamping, b-cell function in patients remained significantly impaired in comparison with non-obese control subjects (Dutia et al 2014). In our in situ pancreatic perfusion experiment, first-phase insulin secretion was improved in the GK groups, which is encouraging because the major defect of b-cell function in GK rats is first-phase insulin secretion (Oger-Roussel et al 2013). However, both basal and first-phase insulin secretion were still significantly lower than levels in Wistar.…”
Section: Discussionsupporting
confidence: 54%
“…glucose clamping, b-cell function in patients remained significantly impaired in comparison with non-obese control subjects (Dutia et al 2014). In our in situ pancreatic perfusion experiment, first-phase insulin secretion was improved in the GK groups, which is encouraging because the major defect of b-cell function in GK rats is first-phase insulin secretion (Oger-Roussel et al 2013). However, both basal and first-phase insulin secretion were still significantly lower than levels in Wistar.…”
Section: Discussionsupporting
confidence: 54%
“…Other investigators also did not observe changes in cystometric parameters in 10‐week‐old Goto‐Kakizaki rats, whereas they noted increased BC, voided volume and bladder compliance accompanied by reduced micturition threshold and peak pressure at 46‐week‐old animals; of note, the changes in the latter group occurred in the absence of bladder hypertrophy. A third study in 18‐week‐old Goto‐Kakizaki rats reported increased BC and micturition volume, unchanged basal or threshold pressure and voiding efficiency and lowered micturition frequency; frequency and amplitude of non‐voiding contractions was increased . Acute administration of the muscarinic receptor antagonist solifenacin similarly reduced micturition pressure in both strains whereas it reduced duration of micturition only in control and not in diabetic animals.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 92%
“…Hereditary models of T2DM include the Goto‐Kakizaki rat, a model with moderately increased blood glucose levels (Supplementary Table S1). Three studies have reported on bladder hypertrophy in Goto‐Kakizaki rats as compared to an euglycemic control strain, having looked at 12 and 70 weeks, 10 and 46 weeks, or 18 weeks old animals . They report a BW of 88‐132% of control and a BBW of 104‐131% of control (Figure , Supplementary Table S1), that is, only moderate if any enlargement.…”
Section: Comparison Of Hypertrophy Among Models Of Type 2 Diabetesmentioning
confidence: 99%
“…Basic scientific studies indicate that increased oxidative stress and reduced nitric oxide (NO) bioavailability are the major derangements underlying the development and progression of vasculogenic and neurogenic ED associated with DM (Long et al, 2012; Vernet et al, 1995; Luttrell et al, 2008; Carneiro et al, 2010; Elliati et al, 2013; Albersen et al, 2011; Chiou et al, 2010; Oger et al, 2014; Kataoka et al 2014; Musicki et al, 2016; Xie et al, 2007; Kovanecz et al, 2009; Chitaley 2009; Nunes et al, 2015; Wingard et al, 2007; Sanchez et al, 2012). In diabetic patients ED is similarly related to reduced NOS activity, as evidenced by elevated arginase activity (Bivalacqua et al, 2001) and decreased nNOS protein expression (Dashwood et al, 2011), nitrate/nitrite (Tuncayengin et al, 2003) and cGMP content (Angulo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%